Formation of ferrospinel layer at the corroded interface between Al2O3‐spinel refractory and molten steel in RH refining ladle. Issue 11 (9th July 2021) - Chen, Junfeng; Cheng, Yaping; Li, Yuanyuan; Xiao, Junli; Zhang, Yu; Liu, Guangping; Wei, Yaowu; Li, Guangqiang; Zhang, Shaowei; Li, Nan
Abstract: Refining ladle is generally the last inclusion‐removal vessel before the continuous casting of steel, so, it has a vital effect on the final steel quality. In this work, degradation process of a cement‐free Al2 O3 ‐MgAl2 O4 refractory in contact with molten steel/slag in the metal bath area of a Ruhrstahl Heraeus (RH) refining ladle was investigated. A reaction product layer with the formation of ferrospinel (hercynite) and Fe‐rich phases was observed, suggesting that the interactions/reactions between the refractory lining and the molten steel should also be considered to have a better understanding of overall degradation mechanism of the refractory served under the RH refining conditions. The two types of alumina grains in the refractory, sintered and fused alumina, were attacked in an active way and a passive way, respectively. The effect of the crack generation and steel infiltration on degradation of the refractory was also discussed in detail, based on the microstructural characterizations.